Spatial and Temporal Electrodynamics in Acuzones: Test-Induced Kinematics and Synchronous Structuring. Phenomenological Study - Yuri F. Babich; Andrey Y. Babich (MEDrang Inc., 2021)
Background So far there is no confidence in the basics of acupoint/meridian phenomena, specifically in spatial and temporal electrical manifestations in the skin. Methods Using the skin electrodynamic introscopy, the skin areas of 32 × 64 mm2 were monitored for spectral electrical impedance landscape with spatial resolution of 1 mm, at 2 kHz and 1 MHz frequencies. The detailed baseline and 2D test-induced 2 kHz-impedance phase dynamics and the 4-parameter time plots of dozens of individual points in the St32-34 regions were examined in a healthy participant and a patient with mild gastritis. Non-thermal stimuli were used: (1) (for the sick subject), microwaves and ultraviolet radiation applied alternately from opposite directions of the meridian; and (2) (for the healthy one) microwaves to St17, and cathodic/anodic stimulation of the outermost St45, alternately. Results In both cases, the following phenomena have been observed: emergence of in-phase and/or antiphase coherent structures, exceeding the acupoint conditional size of 1 cm; collective movement along the meridian; reversible with a reversed stimulus; counter-directional dynamics of both whole structures and adjacent points; local abnormalities in sensitivity and dynamics of the 1 MHz and 2 kHz parameters indicating existence of different waveguide paths. Conclusion It is assumed that these findings necessitate reconsideration of some basic methodological issues regarding neurogenic/acupuncture points as spatial and temporal phenomena; this requires development of an appropriate approach for identifying the acuzones patterns. These findings may be used for developing new approaches to personalized/controlled therapy/treatment.